Please answer question from photo
![Please answer question from photo class=](https://us-static.z-dn.net/files/d59/9055ed000935d9634d07fda44d6e73c9.png)
Answer:
[tex]y=-1[/tex]
Step-by-step explanation:
We have been given an equation [tex]y=-2x+1[/tex]. We are asked to complete the given table using our given equation.
We can see that our given table has two columns namely x and y.
To find the value of y for given values of x, we need to substitute the given x value in our equation.
Substituting [tex]x=0[/tex] in our equation we will get,
[tex]y=-2*0+1[/tex]
[tex]y=0+1[/tex]
[tex]y=1[/tex]
Therefore, the value of y for first row is 1 and ordered pair will be (0,1).
Substituting [tex]x=-3[/tex] in our equation we will get,
[tex]y=-2*-3+1[/tex]
[tex]y=6+1[/tex]
[tex]y=7[/tex]
Therefore, the value of y for 2nd row is 7 and ordered pair will be (-3,7).
Substituting [tex]x=1[/tex] in our equation we will get,
[tex]y=-2*1+1[/tex]
[tex]y=-2+1[/tex]
[tex]y=-1[/tex]
Therefore, the value of y for 3rd row is [tex]-1[/tex] and ordered pair will be (1,-1).